2023
DOI: 10.1111/odi.14617
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells‐derived IL‐6 promotes invasion and metastasis of oral squamous cell carcinoma via JAK‐STAT3 signalling

Abstract: ObjectivesOral squamous cell carcinoma (OSCC) is often diagnosed with cervical lymph node metastasis. Mesenchymal stem cells (MSCs) and interleukin‐6 (IL‐6) signalling are considered to play important roles in promoting tumour malignancy. The detailed biological interaction of MSCs and IL‐6 and the subsequent effect on OSCC metastasis remain largely unclear. This study aimed to determine the effects and molecular mechanism of MSCs‐derived IL‐6 on tumour invasion and metastasis.Subjects and MethodsThe effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Zhang et al [27] found that OSCC oncogenes activate the JAK/STAT3 pathway by promoting JAK2 and STAT3 phosphorylation, which ultimately induces the metastasis of OSCC cells [27]. As reported by Liu et al [28], the activation of the JAK/STAT3 signaling pathway facilitated OSCC oncogenicity and metastasis. Alain et al…”
Section: Discussionmentioning
confidence: 96%
“…Zhang et al [27] found that OSCC oncogenes activate the JAK/STAT3 pathway by promoting JAK2 and STAT3 phosphorylation, which ultimately induces the metastasis of OSCC cells [27]. As reported by Liu et al [28], the activation of the JAK/STAT3 signaling pathway facilitated OSCC oncogenicity and metastasis. Alain et al…”
Section: Discussionmentioning
confidence: 96%
“…STATs are ignited by the Janus-associated kinases (JAKs) [6]. In bacterial-infected and inflamed oral cavity, JAKs can be triggered by F. nucleatum and P. gingivalis [43,46] or upon the binding of IL-1β, IL-6, IL-8, TNF-α, EGF, or TGF-β to their membrane receptors [81][82][83][84][85][86][87]. In this context, it must be underlined that, while they directly activate the JAKs, F. nucleatum and P. gingivalis stimulate OSCC cells to produce the abovementioned JAK-activating cytokines [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Effects Of P Gingivalis and F Nucleatum Leading To The Onset...mentioning
confidence: 99%
“…Among STAT family members, STAT3 is over-activated in OSCCs, where it strengthens the viability and promotes the proliferation of OSCC cells [82,83,86,90].…”
Section: Effects Of P Gingivalis and F Nucleatum Leading To The Onset...mentioning
confidence: 99%